Successful nurse communication : safe care, healthy workplaces, & rewarding careers - Boynton, Beth (Philadelphia : F.A. Davis Company, 2022)
'Explore all of the critical ways your ability to communicate successfully can positively impact not only nurse-client, nurse-family, and colleague-colleague relationships, but also your ability to make the work environment less stressful and to manage professional and personal challenges, even in a world still reeling from the impact of the pandemic. Step by step, you'll build the essential communication skills you need, with an emphasis on developing the emotional intelligence necessary to speak assertively and listen respectfully in the high-stakes, high-pressure environments where nurses work.'
Previous edition: 2016.
Includes bibliographical references and index.
Print version record.
WorldCat record variable field(s) change: 050, 650
Keywords: Communication in nursing; Nurse and patient; Nursing -- Methods; Communication; Nurse-Patient Relations; Communication en soins infirmiers; Relations infirmière-patient.; Communication in nursing; Nurse and patient